(untitled) (International Journal of Engineering and Computer Science, 2013)
Flash crowd are unexpected, when the attackers is to simulate the traffic patterns of flash troops to fly below the radar. In such a case, use similarity based detection method analyzes of network packets that share the same designation address as one network flow. The network packets are clustered and the flows of network packets are analyzed, the information of flow of packets are stored in a database. The network packets are transmitting from the source to designation is through router. In router, authentications may be analyzed when the network packets are authenticated. If this is a chance of anonymous networks packets while enters into the router, the alarm is fixed and intimate to the router not to allow the packets within it. Majorly the flash crowds’ attacks are leads to the distributed denial of services attacks. DDos bout flow can be distinguished from ostentatious crowds by the flow correlation coefficient at edge router, the length of the sampled flow is satisfactorilyhuge and the DDos boutforte is satisfactorily strong. This algorithm examines the router value based on method Similarity based detection method stored in the database. The research work includes the concepts of flash crowd, router value and analyzes the information based on router value.